Victorian Hallucinogens - Zieger, Susan (Romanticism and Victorianism on the Net)

(untitled) (Université de Montréal, 2008)
AbstractNineteenth-century British, U.S., and European writings about the hallucinogenic drugs peyote and mescaline in anthropological, medical, and general interest journals appropriated the drugs from the context of Native American rituals. Appealing primarily to vision, which was commonly understood to be the most intellectual of the senses, and generating sensations of omniscience and self-reflexivity, these drugs became the occasion for their writers’ fantasies of intellectual transcendence and concomitant disembodiment. These fantasies tacitly promoted the imperial, raced, classed, and gendered power of the elite hallucinogenic subject. They also connected with similar fin-de-siècle practices of consumption, including Aesthetic delight in the refinement of visual experience and in the collection of obscure global artifacts, and the passive consumption of media entertainment such as kaleidoscopes, phantasmagoria, and cinema. Although not numerous, hallucinogenic writings should be considered part of the culture of visual modernity that helped shape subjectivities at the turn of the century.